Investigation on current situation of Chinese patent medicines for children in China based on the national drug coding database - Liu, Hui; Rong, Ping; Zhang, Yatong; You, Yuqiong; Fu, Qianfang; Cai, Lili; Wei, Juan; Ma, Rong (Frontiers in Pharmacology, 2025)
IntroductionChinese patent medicine is a crucial component of traditional Chinese medicine, significantly promoting public health. Despite the extensive research on Chinese patent medicine for children, various issues persist in its application. Leveraging the national drug coding standard code database of the National Medical Products Administration (NMPA), this investigation delved into the accessibility of Chinese patent medicines tailored for children, offering a comprehensive overview of the current landscape in China. This analysis serves as a valuable resource for formulating targeted policies to promote the use of Chinese patent medicines for children, guiding drug selection, and facilitating the development of pediatric pharmaceuticals.MethodsTaking Chinese patent medicines with “National Medicine Approval Number Z” and “National Medicine Approval Number B” from the NMPA National Drug Coding Database as the research subjects, this study systematically analyzed the distribution, characteristics, and existing issues of Chinese patent medicines for children using descriptive statistical methods.Results and discussionAs of May 2023, 8,903 approved “National Medicine Approval Number Z” Chinese patent medicines, 951 approved “National Medicine Approval Number B” Chinese patent medicines in China, with 1,164 Chinese patent medicines for children identified. Chinese patent medicines for children are predominantly administered orally (92.87%), while external preparations are limited. The taste profile is primarily bitter or sweet, with some medications having other undesirable flavors. The therapeutic focus is skewed toward pulmonary system diseases (31.9%) and spleen-stomach diseases (26.5%). Notably, 49.66% of the medications mention Western medical disease names, and 63.92% reference traditional Chinese medicine (TCM) syndrome types. Critical gaps include unclear age-specific dosage instructions (56.70%), lack of specified treatment duration (92.01%), and incomplete safety information, with adverse reactions mainly involving the gastrointestinal system. Current issues include the limited availability of Chinese patent medicines for children, poor suitability for children, imbalanced research and supply (over-concentration in pulmonary and spleen-stomach disorders), and inadequate safety labeling in drug instructions, posing potential risks. Recommendations include developing new Chinese patent medicines for children, improving drug suitability, conducting post-marketing evaluations, and refining drug labeling to ensure safe and rational pediatric medication use.